THE QUALITY OF LIFE IN PERSONS WITH BEHAVIOURAL PROBLEMS IN PROFESSIONAL INSTITUTES IN THE CZECH REPUBLIC - Ruzicka, Michal (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The objective of the article is to make the reader acquainted with the quality of life in persons with behavioural impairment in professional institutes in the Czech Republic. The first part of the text aims at describing individual institutes, and the second part presents the research conducted in facilities of subsequent care for people with behavioural problems. The system of facilities for the monitored target group is rather extensive. Such facilities are regarded from various perspectives and points of view. The monitored institutes are divided in terms of the age of their clients, the scale of the problems, the services provided, etc. Also, the knowledge of valid legislation plays an important role. The following text intends to divide the target facilities based on specific criteria – which will improve orientation (at first sight) in the complicated and disorganised portfolio of institutes. It is beyond the capacity of this paper to enumerate all institutes dealing in the prevention, intervention, therapy and resocialization of persons with problems relating to behaviour, thinking, emotions, etc. The text adverts to the most significant institutes and introduces their activities in the form of practical examples (casuistry). The paper follows, above all, the current legislation and practice. The presented research focuses on describing the quality of life in persons under the programmes of subsequent care. The reason for selecting this type of institute is the fact that the participants of subsequent care programmes have experience with stays even in other types of monitored facilities.